The effect of ellagic acid on the repair process of periodontal defects related to experimental periodontitis in rats - Figen ÖNGÖZ DEDE; Şeyma BOZKURT DOĞAN; Umut BALLI; Mustafa Cenk DURMUŞLAR; Bahattin AVCI; Kanat GÜLLE; Meryem AKPOLAT FERAH (University of São Paulo, 2021)
Abstract Objective This study aims to evaluate the effect of ellagic acid (EA) by measuring the levels of alveolar bone resorption and inflammatory and oxidative stress markers in the periodontal tissues and serum on the periodontal repair process related to experimental periodontitis in rats. Methodology Forty Wistar rats were divided into four study groups as follows: Group 1=healthy control (n=10); Group 2=EA control (15 mg/kg)(n=10); Group 3=periodontitis (n=10); Group 4=periodontitis+EA (15 mg/kg) (n=10). The periodontitis model was established by ligating bilateral mandibular first molars for 14 days. Then, rats were given normal saline or EA for another 14 days by gavage administration. Serum and gingiva myeloperoxidase (MPO) activity, 8-hydroxydeoxyguanosine(8-OHdG), and glutathione (GSH) levels were analyzed by ELISA. İmmunohistochemical analysis was used to detect Interleukin (IL)-6, IL-10, and tumor necrosis factor-alpha (TNF-α) immunoreactivities in the periodontal tissues. Alveolar bone loss (ABL) and attachment loss (AL) was evaluated by histomorphometry analysis. Results ABL and AL were statistically higher in group 3 than in groups 1, 2 and 4 and in group 4 than in groups 1 and 2 (p<0.05). MPO activities in gingival tissue and serum were significantly increased in group 3 compared to groups 1 and 2 (p<0.05). Significantly higher serum GSH levels, lower gingiva, and serum 8-OHdG levels, and MPO activity were observed in group 4 compared to group 3 (p<0.05). Rats with periodontitis (group 3) expressed significantly higher immunoreactivities of IL-6 and TNF-α and lower IL-10 immunoreactivity compared to those other groups (p<0.05). IL-6 and TNF-α immunoreactivities significantly decreased and IL-10 immunoreactivity increased in group 4 after the use of EA compared to group 3 (p<0.001). Conclusions Our findings showed that EA provides significant improvements on gingival oxidative stress and inflammatory markers and alveolar bone resorption in the repair process associated with experimental periodontitis. Therefore, EA may have a therapeutic potential on periodontitis.